2018
DOI: 10.1104/pp.17.01636
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Sulfide Increases Production of NADPH Oxidase-Dependent Hydrogen Peroxide and Phospholipase D-Derived Phosphatidic Acid in Guard Cell Signaling

Abstract: Hydrogen sulfide (HS) is an important gaseous signaling molecule in plants that participates in stress responses and development. l-Cys desulfhydrase 1, one of the enzymatic sources of HS in plants, participates in abscisic acid-induced stomatal closure. We combined pharmacological and genetic approaches to elucidate the involvement of HS in stomatal closure and the interplay between HS and other second messengers of the guard cell signaling network, such as hydrogen peroxide (HO) and phospholipase D (PLD)-der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
71
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(75 citation statements)
references
References 56 publications
3
71
0
1
Order By: Relevance
“…Following from HyPer, new sensors based on redox relays are being designed. A fusion of roGFP2 with the yeast thiol peroxidase (TPX) Orp1 (roGFP2‐Orp1) allows H 2 O 2 ‐dependent oxidation of roGFP2 (Gutscher et al ., ; Scuffi et al ., ). roGFP2‐Orp1 is promising because, unlike HyPer, it is not pH sensitive.…”
Section: Measurement and Imaging Of H2o2mentioning
confidence: 97%
“…Following from HyPer, new sensors based on redox relays are being designed. A fusion of roGFP2 with the yeast thiol peroxidase (TPX) Orp1 (roGFP2‐Orp1) allows H 2 O 2 ‐dependent oxidation of roGFP2 (Gutscher et al ., ; Scuffi et al ., ). roGFP2‐Orp1 is promising because, unlike HyPer, it is not pH sensitive.…”
Section: Measurement and Imaging Of H2o2mentioning
confidence: 97%
“…RoGFP2‐Orp1 was exploited to monitor H 2 O 2 dynamics in yeast (Bode et al ., ), Drosophila (Albrecht et al ., ) and human cells (Gutscher et al ., ; Sobotta et al ., ). Very recently the cytosolic construct was introduced into Cyclamen persicum (Ratjens et al ., ), and we have previously used it in Arabidopsis guard cells (Scuffi et al ., ). Nevertheless, detailed characterisation of the sensor in plants and its application in different cell compartments has been lacking.…”
Section: Introductionmentioning
confidence: 97%
“…It has been reported that DES1 catalyzes the desulfuration of l ‐cysteine to H 2 S, ammonia and pyruvate in the cytosol (Álvarez et al, ), and the former is a highly reactive molecule that has been proposed as gasotransmitter in mammals (Mazza, Pasqua, Cerra, Angelone, & Gattuso, ). In higher plants, the increasing evidence has shown that DES1/H 2 S is involved in adaptations and phytohormone responses (García‐Mata & Lamattina, ; Guo et al, ; Lisjak et al, ; Munaron, Avanzato, Moccia, & Mancardi, ; Scuffi et al, ). DES1/H 2 S has been identified as an essential component of the complex signaling network in multiple ABA responses (Jin et al, ; Scuffi et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Although the null mutants of DES1 showed an approximately 30% decrease in total DES activity, it was clearly demonstrated that DES1 expression was hormonally regulated. Importantly, DES1-produced H 2 S acts early in ABA-dependent stomatal closure and interacts with other second messengers or protein kinases to relay the guard cell signaling network, such as NO, ROS, and MAP kinase as well (Corpas, González-Gordo, Cañas, & Palma, 2019;Du et al, 2019;Scuffi et al, 2014Scuffi et al, , 2018.…”
Section: Introductionmentioning
confidence: 99%